(untitled) (Journal of the Bangladesh Agricultural University, 2016)
The presence of formalin and ethepon was investigated in some fruits viz. Apple, Banana and Mango collected from three local markets viz. Bangladesh Agricultural University (BAU) KR Market, BAU Shesh More market and Notun Bazar of Mymensingh Sadar. Samples were analyzed by gas chromatograph coupled with flame ionization detector. Data were tested in indentical condition with proper calibration of the instrument. Of the samples, 67 percent were free from both chemicals. About 10 ppm formalin was detected in the apple samples of BAU Shesh More. In contrast, 32 ppm ethepon was quantified in the banana samples of BAU KR market. J. Bangladesh Agril. Univ. 13(1): 7-12, June 2015